Public health and welfare concepts, methodologies, tools, and applications (Information Science Reference, 2017)
"The prevention and treatment of diseases is a primary concern for any nation in modern society. To maintain an effective public health system, procedures and infrastructure must be analyzed and enhanced accordingly. [This book] provides a comprehensive overview of the latest research perspectives on public health initiatives and promotion efforts"--Provided by publisher.